PENGARUH KENAIKAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN FREE CASH FLOW DAN PERTUMBUHAN SEBAGAI VARIABEL PEMODERASI - Wijayanti, Handayani Tri (Riset Manajemen & Akuntansi, 2010)
The company managements often conducts profit engineering that is usually called as earnings management. This research attempts to describe whether there is or not the effect of leverage on earnings management with free cash flow and growth as the moderating variable. The research taken 41 manufacturing companies listed in Indonesian Stock Exchange as the sample from 2003 to 2007. The sampling process was done purposive sampling method while data collection was achieved through the documentation method of Indonesian Stock Exchange (www.jsx.co.id), âPojok BEJ (Indonesian Stock Exchange Corner)â of Surakarta Sebelas Maret University and ICMD (Indonesian Capital Market Directory). The earnings management in this research was measured using Modified Jones Model. The result of research shows that the leverage in fact does not affect the earnings management. Earnings management is affected by free cash flow, size (company size), and interaction leverage and growth. The result of hypothesis 2 testing shows that H2 is not supported, indicating that the free cash flow is rejected as the moderating variabel, but when the free cash flow is tested separately, the different result shows that it in fact affects the earnings management. Hypothesis 3 is accepted, where there is interaction between leverage and growth to effect earnings management.